植物甾醇的抗炎性研究进展Progress on anti-inflammatory properties of phytosterols - 刘雅谦，李琳，孙万成，罗毅皓 LIU Yaqian, LI Lin, SUN Wancheng, LUO Yihao (Zhongguo youzhi, 2022)
植物甾醇作为一种食物来源中的功能性成分，对人体产生有益的影响。近年来，植物甾醇由于其安全性和有效的抗炎活性而受到广泛关注。为系统介绍植物甾醇的抗炎作用，综述了植物甾醇对多种炎症抑制作用的分子机制，包括对细胞因子和其他炎症相关因子、NF-KB信号通路及免疫系统的影响，介绍了植物甾醇对结肠炎、前列腺炎、肝炎及其他炎症的作用。植物甾醇是一种有效抗炎的活性物质，未来仍需系统研究其抗炎分子机制及进行临床研究。As a functional ingredient in food sources, phytosterols have a beneficial effect on the human body. In recent years, phytosterols have received widespread attention due to their safety and effective anti-inflammatory activity. In order to systematically summarize the function in anti-inflammation of phytosterols, the molecular mechanism of the inhibitory effects of phytosterols on various inflammations, including the effects on cytokines and other inflammation related factors, NF-KB signal pathway and immune system, and the effects of phytosterols on colitis, prostatitis, hepatitis and other inflammation were introduced. Phytosterol is an effective anti-inflammatory active substance. In the future, its anti-inflammatory molecular mechanism needs to be studied systematically and the clinical research needs to be carried out.